Automatic weight selection and fixed-structure cascade controller for a quadratic boost converter - Kaitwanidvilai, Somyot; Srithongchai, Pitsanu (My University, 2011)
In this paper, a new technique for designing a robust cascade controller for a quadratic boost converter is proposed. A single performance index in H infinity loop shaping control called stability margin is adopted as the objective function in the proposed optimization control problem; GA is used to solve this problem to evaluate the optimal controller. Necessary conditions of cascade control scheme are adopted as the constraints in the optimization problem. In addition, pre-compensator weight, which is normally difficult to be selected, is simultaneously determined with the controller. Comparative study with the conventional H infinity loop shaping is presented. Finally, simulation results verify the effectiveness of the proposed technique. © 2011 Springer Science+Business Media B.V.
Keywords: Fixed-structure robust control; Genetic algorithm; H infinity loop shaping control; Quadratic boost converter